2013
DOI: 10.1088/0004-637x/771/2/129
|View full text |Cite
|
Sign up to set email alerts
|

The Mass Dependence Between Protoplanetary Disks and Their Stellar Hosts

Abstract: We present a substantial extension of the millimeter (mm) wave continuum photometry catalog for circumstellar dust disks in the Taurus star-forming region, based on a new "snapshot" λ = 1.3 mm survey with the Submillimeter Array. Combining these new data with measurements in the literature, we construct a mm-wave luminosity distribution, f (L mm ), for Class II disks that is statistically complete for stellar hosts with spectral types earlier than M8.5 and has a 3σ depth of roughly 3 mJy. The resulting census … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

95
1,029
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 662 publications
(1,144 citation statements)
references
References 226 publications
95
1,029
9
Order By: Relevance
“…where F ν is the flux density, d is the distance, κ ν is the mass opacity, and B ν (T d ) is the Planck function evaluated at a dust temperature of T d (e.g., Andrews et al 2013). This flux is only sensitive to the small dust grains; in a system with collisionally generated dust grains a substantial amount of mass is locked in meter to km-sized planetesimals that do not emit efficiently at these wavelengths and any mass inferred from the radio emission underestimates the total mass.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…where F ν is the flux density, d is the distance, κ ν is the mass opacity, and B ν (T d ) is the Planck function evaluated at a dust temperature of T d (e.g., Andrews et al 2013). This flux is only sensitive to the small dust grains; in a system with collisionally generated dust grains a substantial amount of mass is locked in meter to km-sized planetesimals that do not emit efficiently at these wavelengths and any mass inferred from the radio emission underestimates the total mass.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…Over the past few decades, there have been numerous studies of nearby star-forming regions at millimeter wavelengths with the aim of measuring disk masses for large samples of disks, and this work has been accelerated in recent years by the power of ALMA to quickly survey large numbers of sources (e.g., Beckwith et al 1990;Osterloh & Beckwith 1995;Dutrey et al 1996;Andrews & Williams 2005, 2007Eisner et al 2008Eisner et al , 2016Mann & Williams 2010;Andrews et al 2013;Mann et al 2014;Ansdell et al 2016Ansdell et al , 2017Barenfeld et al 2016;Pascucci et al 2016). These surveys have tended to target the population of Class II protostar disks because they are no longer embedded in an envelope, and so estimates of their disk masses are more straightforward.…”
Section: Class I Versus Class Ii Disk Massesmentioning
confidence: 99%
“…It has also been shown that Class II disk masses are correlated with stellar mass (Andrews et al 2013, Ansdell et al 2016Barenfeld et al 2016;Pascucci et al 2016). As such, when comparing disk mass distributions, we must take care to ensure that our samples have similar stellar host properties; otherwise, our disk mass measurements may be biased.…”
Section: Class I Versus Class Ii Disk Massesmentioning
confidence: 99%
See 1 more Smart Citation
“…This means it will explore a wider mass range than the radial-velocity and transit techniques. In addition, the binary nature of the host can become a big help as well: Protoplanetary disc masses scale with the central mass, be it a single or binary star (Andrews et al 2013), and heavier discs are expected to produce more gas giants (Mordasini et al 2012). A G dwarf + G dwarf binary, for instance, had a disc mass equivalent to a single A star.…”
Section: Planets Around Non-fgk Binariesmentioning
confidence: 99%